The Value of Mangrove Ecosystems Based on Mangrove Carbon Sequestration in West Kalimantan - Vera Maulidia; Aji Ali Akbar; Jumiati Jumiati; Arifin Arifin; Aini Sulastri (Center for Journal Management and Publication, 2022)
Research on carbon storage is currently in the world spotlight along with the increasing greenhouse effect. Mangroves as one of the ecosystems play a role in blue carbon which can store more carbon than terrestrial forests. Mangroves absorb more carbon than any other forest ecosystem. This is because mangroves are included in wetlands that have the ability to store carbon when the land remains wet. An in-depth discussion was carried out by integrating various literatures on mangroves from 2011–2021 to enrich the information for this research. Mangrove area in West Kalimantan in the period 2011 - 2021 has an area of about 256,586.80 Ha which is dominated by species Brugueira spp., Rhizophora spp., Sonneratia alba, Avicennia spp. Nypa fruticans, Excoecaria agallocha, Xylocarpus moluccensis and Acrostichum speciosum. Human activities, abrasion and sedimentation have caused a decrease in the area of mangrove ecosystems in West Kalimantan. An increase in temperature has a global impact on life on the earth's surface and the environmental conditions of mangroves. The decrease in micropopulation and aboveground biomass causes a decrease in infauna species and biomass, affects nutrient cycles, destroys nurseries, and reduces mangrove ecosystem services. The results show that mangrove carbon storage in the period 2011 - 2021 is 628.10 tons C.ha-1 which has an economic valuation of 3,410.50 US. Efforts to mitigate global warming and trade in mangroves can be carried out through community-based restoration, restoration of forest plantings, integrated coastal ecosystem rehabilitation, and economic approaches.